If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4 + -5 = x Reorder the terms: -4 + -5 + 3x = x Combine like terms: -4 + -5 = -9 -9 + 3x = x Solving -9 + 3x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -9 + 3x + -1x = x + -1x Combine like terms: 3x + -1x = 2x -9 + 2x = x + -1x Combine like terms: x + -1x = 0 -9 + 2x = 0 Add '9' to each side of the equation. -9 + 9 + 2x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 2x = 0 + 9 2x = 0 + 9 Combine like terms: 0 + 9 = 9 2x = 9 Divide each side by '2'. x = 4.5 Simplifying x = 4.5
| 7(x+1)=-14 | | 17-4x=13+x | | -7xb=b-49 | | X-.75X=25 | | x+2+7x=-16 | | x=(y+4)*log(2y+3) | | 3x^2-8x+3y^2+4=0 | | 216z^3-125y^3= | | B/19-7b/19=54/19 | | 4=x/5=3 | | x/x-2-3/x-1=3/(x-2)(x-1) | | u^2-3u*3u-9= | | 3(63y+42)=84+7(21+42) | | -12-y=98 | | X-.75X=20 | | 2(c+1)+c=44 | | A(2+x)+B(x-1)-1=0 | | x*5=-30 | | 1(x+6)=7 | | 3/5/7/10 | | f(x)=-(x-3)(x+11) | | 18-2[x+(-5)]= | | 6x+5x-4=7 | | V-2.5=1.52 | | 6x-76=64 | | X+4x+2x-4x= | | 3x/7=1-2/5x-10/15 | | 7n+3y+5x=74 | | -2y^2+2y=-2 | | 9w+2=7 | | 5/6dividedby2 | | 3x-10x-5/2=20 |